Budd-Chiari Syndrome and Acute Liver Failure: An Uncommon Presentation of Acute Myeloid Leukaemia
Acute liver failure (ALF) is a rare entity, particularly in the context of Budd-Chiari syndrome (BCS). BCS is an uncommon disorder with multiple risk factors, most commonly myeloproliferative disorders. In BCS, active search and exclusion of underlying malignancy is mandatory, particularly in the context of ALF, as it may contraindicate liver transplantation (LT). We present the case of a healthy 29-year-old male, without known risk factors for liver disease, who presented to the emergency department with abdominal pain, ascites, and jaundice. BCS with consequent severe acute liver injury with rapid progression to ALF was diagnosed. The patient was listed for LT. The study of peripheral blood finally revealed myeloid blasts, and flow cytometry showed a population of blast cells with abnormal immunophenotypic profile (CD33+ and myeloperoxidase, MPO+). The bone marrow biopsy showed morphological and immunophenotypic aspects of acute myeloid leukaemia (AML) FAB M1. This diagnosis was considered a formal contraindication to LT, so the patient was delisted. ALF contraindicated rescue chemotherapy and AML contraindicated LT. The patient died 48 h after ICU admission. The search for underlying neoplasia is mandatory in the context of BCS, moreover with associated ALF, as it may limit lifesaving treatments and interventions to supportive and palliative care.